PEMBENTUKAN ETIKA SOSIAL SANTRI DALAM KELAS TAHFIDZ (STUDI KASUS DI RUMAH TAHFIDZ DAARUL QURAN WA AIMMAH RAWAMANGUN, JAKARTA TIMUR) - Muhammad Fathul Kamal; Hilmi Iskandar Rosid; Fauzan Hamdi; Wahyu Abdul Karim; Yayah, Husheini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is grounded in the importance of forming santri's social ethics as an integral part of Qur'an tahfidz learning. Tahfidz activities are not merely oriented toward memorization achievement, but are also directed at internalizing Qur'anic values into santri's social behavior. In practice, however, learning still tends to emphasize memorization targets over the formation of social ethics. This study aims to describe the process of forming santri's social ethics in the tahfidz class, to identify the supporting and inhibiting factors, and to describe the implementation of santri's social ethics in daily life at Rumah Tahfidz Daarul Qur'an Wa Aimmah, Rawamangun, East Jakarta. A qualitative approach with a case study design was employed. Data were obtained through observation, interviews, and documentation involving the foundation's management, ustadz, and santri, then analyzed through data reduction, data display, and conclusion drawing, while data validity was tested through source, method, time, and theory triangulation. The results show that social ethics formation occurs through the internalization of Qur'anic values, habituation of muroja'ah and sima'an among santri, and the provision of advice and supervision involving ustadz, the foundation's management, and parents. Supporting factors include the ustadz's exemplary conduct, a conducive learning environment, routine tahfidz activities, and synergy between the foundation and the family, while inhibiting factors consist of internal aspects such as laziness and fatigue, and external aspects such as uncontrolled gadget use. The implementation of santri's social ethics is reflected in humility (tawadhu'), respect for teachers and parents, discipline, responsibility, and concern for others.